Optimizing seed certification can boost sustainable agriculture: The case of Nigeria - Spielman, David J.; Takeshima, Hiroyuki; Hunt, Adam (CGIAR, 2024)
In the quest for agricultural productivity and food security, Nigeria has made significant strides in expanding the production and distribution of certified seeds for crops like maize, rice, and, to some extent, cowpea. However, a recent study by the International Food Policy Research Institute (IFPRI) and the International Institute of Tropical Agriculture (IITA), conducted under the CGIAR Seed Equal Initiative, highlights the need for a more nuanced approach to seed certification. The recommendations come in light of findings that an indiscriminate expansion of the current system may face diminishing returns.